From Genome-Wide Association Studies to Cardiac Electrophysiology: Through the Maze of Biological Complexity - Scholman, Koen T.; Meijborg, Veronique M. F.; Gálvez-Montón, Carolina; Lodder, Elisabeth M.; Boukens, Bastiaan J. (Frontiers in Physiology, 2020)
Genome Wide Association Studies (GWAS) have provided an enormous amount of data on genomic loci associated with cardiac electrophysiology and arrhythmias. Clinical relevance, however, remains unclear since GWAS do not provide a mechanistic explanation for this association. Determining the electrophysiological relevance of variants for arrhythmias would aid development of risk stratification models for patients with arrhythmias. In this review, we give an overview of genetic variants related to ECG intervals and arrhythmogenic pathologies and discuss how these variants may influence cardiac electrophysiology and the occurrence of arrhythmias.